2018
DOI: 10.1039/c7fo00088j
|View full text |Cite
|
Sign up to set email alerts
|

Association between sn-2 fatty acid profiles of breast milk and development of the infant intestinal microbiome

Abstract: Increasing evidence shows that host diet and gut microbes are related. Previous studies have shown the effects of specific dietary fatty acids (FAs) on intestinal microbiota, but little is known about the effect of the stereospecifically numbered sn-2 position in triglycerides (TG) of human milk on the gut microbiome of infants. This study aimed at examining possible effects of sn-2 FAs of human milk on the gut microbial development of breastfeeding babies. Sn-2 FAs and intestinal microbiota were assessed by G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…Compared to sn-1,3 palmitic acids of triglycerides, sn-2 palmitic acids resulted in decreased intestinal injury and inflammation by upregulation of PPAR-γ, antioxidant enzymes (superoxide dismutase, glutathione peroxidase), and induction of an immunosuppressive T-regulatory cell response [43]. These data support the role of the saturated fatty acid, palmitic acid, specifically in sn-2 configuration, as being important for intestinal mucosal homeostasis, gut microbiome, and immune response [44]. However, the lack of evidence in clinical trials to establish a cause and effect relationship between the palmitic acid at sn-2 position and neonatal health outcomes, led the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition to recommend that the inclusion of high sn-2 palmitic acid cannot be considered essential in human infant formula [45,46].…”
Section: Saturated and Monounsaturated Fatty Acidssupporting
confidence: 52%
“…Compared to sn-1,3 palmitic acids of triglycerides, sn-2 palmitic acids resulted in decreased intestinal injury and inflammation by upregulation of PPAR-γ, antioxidant enzymes (superoxide dismutase, glutathione peroxidase), and induction of an immunosuppressive T-regulatory cell response [43]. These data support the role of the saturated fatty acid, palmitic acid, specifically in sn-2 configuration, as being important for intestinal mucosal homeostasis, gut microbiome, and immune response [44]. However, the lack of evidence in clinical trials to establish a cause and effect relationship between the palmitic acid at sn-2 position and neonatal health outcomes, led the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition to recommend that the inclusion of high sn-2 palmitic acid cannot be considered essential in human infant formula [45,46].…”
Section: Saturated and Monounsaturated Fatty Acidssupporting
confidence: 52%
“…Abundances of SCFA-producing bacteria were reduced in Canadian HEU children compared with Canadian HUU children. We found that gut microbiomes of Canadian HEU children had lower relative abundances of SCFA-producing taxa that have been isolated from breast milk and are associated with breastfeeding-Bifidobacterium and Veillonella (36,37). As well, other prominent SCFA producers normally present in adult microbiomes, Ruminococcus, Lachnospira, Clostridia, Faecalibacterium, and Roseburia (38), were also less abundant in Canadian HEU children.…”
Section: Discussionmentioning
confidence: 76%
“…They are detergents for bacteria explaining, at least in part, the low bacterial count in the duodenum where bile acids are mostly released. Human milk fatty acid profiles were associated with the relative abundance of five taxa ( Bacteroides , Enterobacteriaceae, Veillonella, Streptococcus , and Clostridium ) in the gut microbiota of breastfed neonates (97).…”
Section: Breastfeeding Shapes Gut Microbiota Composition and Metabolismmentioning
confidence: 99%